Zwei Wörter mit langer Gewaltgeschichte: Compelle intrare (Lk 14,23) - Felber, Anneliese (Protokolle zur Bibel, 2009)
Augustine interpretes Luke 14:23 (compelle intrare) in the light of his conflict with the Donatist movement in Roman North Africa. Therefore violence to the Donatists by the imperial authorities seems to be justified. Through the centuries scholars have used Augustine’s biblical interpretation selectively as a norm against people of a different faith.